Characterization of Planktonic Foraminifera in the Cretaceous, Phosphatic Nodules from District Tiruchirappalli, Tamil Nadu, India: Implications for the Biological Approach - Hussain , Ajhar; Fatima , Nuzhat; Hasan , Mohammad; Khan , Mohd Faisal (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The onshore Cretaceous marine sedimentary sequence of the phosphatic nodules is exposed in the Tiruchirappalli district of Tamil Nadu. The surface of the nodules is yellow to reddish ferruginous with light to dark brown phosphate content having veins. The presence of microbial mats, coated grains, and fossils wrap with the association of CFA, calcite, and quartz, associated with phosphatized microbial mats and planktonic foraminifera, are found. The texture/structures appear as algal mats, coated grains and crystal of carbonate fluroapatite in the groundmass. Organic matter in the form of microbial filaments, as revealed by SEM and thin sections studies, indicates the role of micro-organisms involved in the formation of phosphatic nodules from study area. This research contributes significant data on the planktonic foraminifera from Cretaceous phosphatic nodules in Tamil Nadu, India, and demonstrates the potential of a biological approach in deciphering the region's geological history. The findings are pertinent to paleontologists, geologists, and researchers studying Cretaceous marine environments and paleoclimatology, making a valuable addition to the existing body of knowledge in these fields.